The Role of Newspaper Styles in Literature - Kodirova Zarina Bakhodirovna (Genius Journals, 2021)
The article specifically focused on a study of newspapers, detailed classifications of newspaper styles by different scientists. Moreover, the research analyses the role of newspaper styles in modern literature as well as comparing it with historical newspapers and provides information about functional styles and its peculiarities in literature. Each newspaper article has its particular style in written discourse, consequently to analyze newspaper styles, details of literary writings should be researched as well. Stylistic features of the newspaper language and the headlines are as well studied in the following article
Keywords: scientists; literature; historical; Newspaper